NF-κB Duplications in the Promoter-Variant HIV-1C LTR Impact Inflammation Without Altering Viral Replication in the Context of Simian Human Immunodeficiency Viruses and Opioid-Exposure - Dave, Rajnish S.; Ali, Haider; Sil, Susmita; Knight, Lindsey A.; Pandey, Kabita; Madduri, Lepakshe S. V.; Qiu, Fang; Ranga, Udaykumar; Buch, Shilpa; Byrareddy, Siddappa N. (Frontiers in Immunology, 2020)
Recent spread of the promoter variant (4-κB) Human immunodeficiency virus-1 clade C (HIV-1C) strain is attributed to duplication of the Nuclear Factor Kappa B (NF-κB) binding sites and potential increased heroin consumption in India. To study the underlying biology of 4-κB HIV-1C in rhesus macaques, we engineered a promoter-chimera variant (4NF-κB) Simian Human Immunodeficiency Virus (SHIV) by substituting the HIV-1C Long Terminal Repeat (LTR) region consisting of 4 NF-κB and 3 Sp-1 sites with the corresponding segment in the LTR of SHIV AD8EO. The wild-type (3NF-κB) promoter-chimera SHIV was generated by inactivating the 5’ proximal NF-κB binding site in SHIV 4NF-κB. CD8-depleted rhesus macaque PBMCs (RM-PBMCs) were infected with the promoter-chimera and AD8EO SHIVs to determine the effects of opioid-exposure on inflammation, NF-κB activation, neurotoxicity in neuronal cells and viral replication. Morphine-exposure of RM-PBMCs infected with SHIVs 4NF-κB, 3NF-κB and AD8EO altered cellular transcript levels of monocyte chemoattractant protein 1, interleukin 6, interleukin 1β and Tumor Necrosis Factor α. Of note, divergent alteration of the cytokine transcript levels was observed with these promoter-chimera wild-type and variant SHIVs. NF-κB activation was observed during infection of all three SHIVs with morphine-exposure. Finally, we observed that SHIV AD8EO infection and exposure to both morphine and naloxone had the greatest impact on the neurotoxicity. The promoter-chimera SHIV 4NF-κB and SHIV 3NF-κB did not have a similar effect on neurotoxicity as compared to SHIV AD8EO. All SHIVs replicated efficiently at comparable levels in RM-PBMCs and morphine-exposure did not alter viral replication kinetics. Future in vivo studies in rhesus macaques will provide greater understanding of 4-κB HIV-1C viral immunopathogenesis and onset of disease in the central nervous system during morphine-exposure.